2018
DOI: 10.22159/ajpcr.2018.v11i9.26487
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Urban and Rural Population of Greater Noida National Capital Region of India

Abstract: Objective: The objective of this study was to evaluate the prevalence of metabolic syndrome (MetS) and to define its predictors in urban and rural patients presenting to tertiary care hospitals located in Greater Noida district Gautam Budh Nagar, India.Methods: A total of 367 participants recruited in the study, aged 20–55 years, comprising, 290 patients (149 rural and 141 urban) and 77 healthy age, sex-matched controls from the study area. Anthropometric, clinical and laboratory examination information was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A recent large study 32 conducted in the adjoining state of Kerala reported significantly higher prevalence in adult participants living in urban (26%) than in rural areas (22%). Similarly, a study 40 in the national capital region of India reported urban prevalence (NCEP ATP-III) as 21.7% in male participants and 27.8% in female participants, whereas corresponding numbers for rural sites were 13.8% and 18.8%. Kapil et al 27 reported 28.6% prevalence among individuals aged 60 and above from a rural community from a high-altitude region in district of Nainital in northern India, based on the IDF criteria.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent large study 32 conducted in the adjoining state of Kerala reported significantly higher prevalence in adult participants living in urban (26%) than in rural areas (22%). Similarly, a study 40 in the national capital region of India reported urban prevalence (NCEP ATP-III) as 21.7% in male participants and 27.8% in female participants, whereas corresponding numbers for rural sites were 13.8% and 18.8%. Kapil et al 27 reported 28.6% prevalence among individuals aged 60 and above from a rural community from a high-altitude region in district of Nainital in northern India, based on the IDF criteria.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding gender differences, our study revealed that rural women had a significantly higher prevalence of metabolic syndrome than rural men, whereas this gender difference was not significant in the urban population. A considerable number of previous studies from different parts of India, both in urban 32 , 40 , 42 as well as rural 32 , 33 , 40 , 43 settings, have also shown that metabolic syndrome prevalence is higher in female participants than male participants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation